PREDISPOSING FACTORS INFLUENCING OCCURRENCE OF DOWNER COW SYNDROME IN DAIRY ANIMALS IN SELECTED DISTRICTS OF TAMIL NADU - V. Senthilkumar; A. Mohamed Safiullah; G. Kathiravan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A study was conducted to assess the factors inÀuencing the occurrence of downer cow syndrome in Tamil Nadu. For this, primary data from the 67 dairy farmers (60 cow and 07 buffalo farmers) from Namakkal and Karur districts of Tamil Nadu having downer cow syndrome affected dairy animals were collected. Using logistic regression model, Wald statistic were obtained for the independent variables which indicated that the coefficients for parity, stage of lactation, summer and winter season, previous occurrence of metabolic diseases, feeding of green fodder, feeding of concentrate, proximity to parturition (near term) and species of dairy animal were observed significant. The log odds of the animal going to be affected by downer cow syndrome enhanced by 8.199 and 4.581, when parity and mid-stage of lactation were changed from 0 to 1. These findings suggested that more concentration on these factors were warranted to minimise the risk of incidence of downer cow syndrome in bovines.